2023
DOI: 10.3758/s13414-023-02786-2
|View full text |Cite
|
Sign up to set email alerts
|

A combined experimental–correlational approach to the construct validity of performance-based and self-report-based measures of sustained attention

Matthew S. Welhaf,
Michael J. Kane

Abstract: The ability to sustain attention is often measured with either objective performance indicators, like within-person RT variability, or subjective self-reports, like mind wandering propensity. A more construct valid approach, however, may be to assess the covariation in these performance and selfreport measures, given that each of these is influenced by different sources of measurement error. If the correlation between performance-variability and self-report measures reflects the sustained attention construct, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
1
1
0
Order By: Relevance
“…There are a few notable results of this analysis. First, overall, TUTs were modestly related to RTsd ( r = .17 [0.14, 0.21]) consistent with previous research (e.g., Unsworth et al, 2021; Welhaf & Kane, 2023a, 2023b). People who reported being off-task more frequently in the SART also showed more inconsistent responding.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…There are a few notable results of this analysis. First, overall, TUTs were modestly related to RTsd ( r = .17 [0.14, 0.21]) consistent with previous research (e.g., Unsworth et al, 2021; Welhaf & Kane, 2023a, 2023b). People who reported being off-task more frequently in the SART also showed more inconsistent responding.…”
Section: Resultssupporting
confidence: 87%
“…Cleaning of SART performance data was handled using the same procedure for each study (note this might differ from data cleaning procedures either reported or unreported in previous papers). First, to ensure participants engaged with the task sufficiently and understood instructions, we removed anyone who had <70% accuracy on the frequent “go” trials (Welhaf & Kane, 2023a, 2023b).…”
Section: Resultsmentioning
confidence: 99%